Faktor-Faktor Yang Mempengaruhi Minat Konsumen Dalam Menggunakan Qris Sebagai Metode Pembayaran Di Kota Bengkulu - Rahma Daniarti; Karona Cahya Susena; Lydia Gustina Putri (Jurnal Akuntansi, Manajemen, Ekonomi Islam, 2024)
QRIS is a digital payment tool issued by Bank Indonesia, using a barcode that is scanned through a digital wallet application to make transactions easier, faster, and safer. The development of payments using QRIS is seen from the increasing data of qris users up to 48 million users from 2022 to March 2024. The purpose of this study was to determine the effect of convenience, security, and speed on consumer interest in using qris as a payment method in Bengkulu city. This research method uses quantitative research type, the sample in this study is the people of Bengkulu city QRIS users who are shopping at ichiban sushi bencolen mall totaling 100 people.The results of multiple linear regression show the equation: Y = 7.067 + 0.168 X1 + 0.198 X2 + 0.625 X3, this illustrates the positive direction of regression, meaning that the variables of convenience (X1), security (X2) and speed (X3) have a positive influence on consumer interest in using QRIS as a payment method in Bengkulu City. The coefficient of determination (R square) from SPSS 25.00 is 0.519. This means that convenience, security, and speed affect consumer interest in using QRIS as a payment method by 51.9% while the remaining 48.1% is influenced by other factors. The t test results at the 0.05 significance level explain that partially X1, X2, and X3 have a significant influence on consumer interest in using QRIS as a payment method in Bengkulu City with a value of X1 0.011, X2 0.006, X3 0.000